Perception, reality, and the adoption of business analytics: Evidence from North American professional sport organizations. (March 2016) - Troilo, Michael; Bouchet, Adrien; Urban, Timothy L.; Sutton, William A.
Abstract: It is well known that professional sports teams have made extensive use of analytics to improve their on-field performance. However, it is not as apparent that these same organizations use analytics to improve performance on the "business" side. The North American professional sports industry is unique in that the teams operate as legal monopolies/duopolies, with very few cities having more than one major-league team in a particular sport. Thus, our intent is to explore the adoption and assessment of business analytics in professional sports organizations. An empirical analysis is conducted concerning management's perception of the effects of business analytics as well as the actual change in financial performance since the adoption of analytics by the organizations. Highlights: We create an Analytics Index that is generalizable beyond this specific context. Managers perceive an increase in revenues as a result of business analytics. Business analytics do increase actual revenues. There are real differences in perceived increases v. actual outcomes by team.